Heparin remodels the microtubule-binding repeat R3 of Tau protein towards fibril-prone conformations. Issue 36 (8th September 2021) - Dong, Xuewei; Qi, Ruxi; Qiao, Qin; Li, Xuhua; Li, Fangying; Wan, Jiaqian; Zhang, Qingwen; Wei, Guanghong
Abstract : Heparin remodels the microtubule-binding repeat R3 of Tau protein towards fibril-prone conformations by increasing chain dimension and intermolecular contact regions. Abstract : Abnormal aggregation of proteins into pathological amyloid fibrils is implicated in a wide range of devastating human neurodegenerative diseases. Intracellular fibrillary inclusions formed by Tau protein are characterized as the hallmark of tauopathies, including Alzheimer's disease and frontotemporal dementia. Heparin has been often used to trigger Tau aggregation in in vitro studies. However, the conformational changes induced by heparin and the underlying mechanism of promotion of Tau aggregation by heparin are not well understood. Structural characterization of Tau oligomers in the early stage of fibrillation is of great importance but remains challenging due to their dynamic and heterogeneous nature. R3, the third microtubule-binding repeat of Tau, contains the fibril-nucleating core (PHF6) and is crucial for Tau aggregation. In this study, utilizing extensive all-atom replica-exchange molecular dynamic simulations, we explored the conformational ensembles of R3 monomer/dimer in the absence and presence of heparin. Our results show that without heparin, both monomeric and dimeric R3 preferentially adopt collapsed β-sheet-containing conformations and PHF6 plays an important role in the formation of interchain β-sheet structures, while in the presence of heparin, R3 can populate relatively extended disordered states where chain dimension is similar to that of R3 in Tau filaments. Through electrostatic, hydrogen-bonding and hydrophobic interactions, heparin has a preference for interacting with residues V306/Q307/K317/K321/H329/H330/K331 which distribute throughout the entire sequence of R3, in turn acting as a template to extend R3 conformations. More importantly, heparin alters intramolecular/intermolecular interaction patterns of R3 and increases the intermolecular contact regions. Our results suggest that heparin remodels the conformations of R3 towards fibril-prone structures by increasing chain dimension and intermolecular contact regions, which may shed light on the atomic mechanism of heparin-induced amyloid fibrillization of Tau protein.